Nonclinical regulatory considerations for investigational new drug applications for regulatory T cell therapies - Dinh, Phuong-Uyen; Mihalcik, Lauren (Frontiers in Medicine, 2025)
Since FDA approval of the first chimeric antigen receptor (CAR) T cell therapy in 2017, the landscape of cell-based therapies has widely expanded. This expansion has encompassed both the types of cell therapies being developed as well as indications beyond oncology. As an example, the number of regulatory T cell (Treg) therapies in development have been steadily increasing, with targeted focus on treatment of autoimmune and inflammatory diseases. The nonclinical development pathway for Treg therapies has relied on leveraging existing regulatory guidance documents for cell and gene therapies, however the lack of Treg specific guidance coupled with often times limited appropriate preclinical models have created regulatory challenges for drug developers. In this review, preclinical considerations for the development of Treg therapies will be described. Specifically, topics will include the following: (1) Current health authority expectations for demonstrating pharmacodynamics, biodistribution, and safety of Treg therapies, including selection of relevant models, assay selection for bioanalytical endpoints, and strategic study planning to maximize study readouts while reducing animal use. (2) Approaches for conducting target liability assessments to supplement nonclinical development packages for indications with limited appropriate preclinical models. (3) Leveraging health authority interactions, such as the US Food and Drug Administration (FDA) Initial Targeted Engagement for Regulatory Advice on CBER/CDER Products (INTERACT) and Pre-Investigational New Drug (Pre-IND) meetings, to gain feedback and actionable directives to guide program development. (4) Guidance on generating high quality nonclinical regulatory documents, including study reports and submission documents, to support IND applications.